(untitled) (Nexus International Journal of Science and Education, 2024)
Play-based learning has gained increasing recognition as an effective pedagogical approach in elementary education, offering students opportunities to engage in active, experiential learning. This research explores the implementation and impact of play-based learning strategies with a specific focus on elementary teachers. The results of the study disclosed considering the first objective of this study is the lived experience of teachers in the implementation of play-based learning in elementary classrooms. Teacher beliefs and attitudes towards play-based learning, and lastly, Implementation of play-based learning in elementary classrooms. The second objective of this study is for the teachers to cope with the implementation of play-based learning in elementary classrooms. Based on the interview data gathered from the teacher’s coping mechanism with the challenges teachers explore in the implementation of play-based learning in elementary classrooms the three major themes such as the impact of play-based learning on student outcomes, Play-based learning and academic achievement, and Play-based learning and curriculum goals. The third objective of this study is to explore educational insight or tools that can be drawn from the study of the play-based learning elementary teachers in focus emerged major themes such as classroom organization and materials, limitations and critical analysis of literature, and the importance of child-centered learning. Further discuss In the future, we should explore and implement more flexible assessment models that align with how classroom layouts, materials, and resources influence the effectiveness of play-based strategies.